Distress as a mediator for pain and activities of daily living in older adults with fibromyalgia - Gower, Caitlin; Trevitt, Jennifer; Cherry, Barbara J.; Zettel-Watson, Laura (Frontiers in Medicine, 2022)
Pain, distress, and activities of daily living impact the lives of those with chronic pain. This study investigated the mediating role of distress on the relationship between two aspects of pain (intensity and interference) and activities of daily living in individuals with fibromyalgia. Using secondary, cross-sectional data collected through the CSUF Fibromyalgia Longitudinal Study, the current investigation focused on data collected from men and women with fibromyalgia who attended the study for the first time between the years of 2008 and 2014. Pain intensity and pain interference were measured on 0-10 Likert-type scales from the National Fibromyalgia Assessment Questionnaire (NFAQ, 2007), while distress was calculated from depression and anxiety scores. The depression component of distress was assessed using the Beck Depression Inventory II (BDI-II). The anxiety component of distress was measured on a 0-10 Likert-type scale from the NFAQ. Activities of daily living (basic and instrumental ADLs) were measured with the Physical Activity Inventory (PAI) scale, which was adapted from the Composite Physical Functioning scale (CPF). It was hypothesized that the relationships between pain intensity and pain interference and activities of daily living in individuals with fibromyalgia would be mediated by the construct of distress while controlling for age. Using SPSS PROCESS, mediation occurred in both models while controlling for age, as predicted. However, those who were older were reporting lower levels of pain intensity and distress than their younger counterparts, which was not predicted. These relationships may be related to time since diagnosis, and that concept is explored. Those with FM struggle with treating their symptoms and improving functionality long before being diagnosed. With these new findings, it is clear that anxiety and depression should be assessed and treated in addition to pain, to improve functionality in this population. Implications and clinical applications are further discussed.